(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study is to provide a qualitative and quantitative explanation of the structure activity relationships with pharmacophore analysis and Quantitative Structure Activity Relationship (QSAR) studies of the compounds synthesized as acetylcholinesterase enzyme inhibitor by our research group.Material and Methods: Maestro 11.9 (Schrödinger, New York) was used for pharmacophore model studies. Pharmacophore analysis was performed for all compounds showing acetylcholine esterase inhibitory effect. For QSAR studies, various physicochemical parameters of these compounds were calculated using GaussView 5.0 and ChemDraw 15.0 programs. Regression analysis was performed by using these parameters and QSAR equation was obtained.Results: All compounds overlapped and hypotheses generated. The most appropriate pharmacophore model was created by comparing the hypothesis and activity results of the compounds. The analyses were performed using 8 different parameters for all compounds. R2 value of equation was found 1. Conclusion: The pharmacophore analysis and the QSAR equation are applicable for all compounds synthesized as acetylcholinasterase inhibitory and containing pyridazinon-2-ylacetohydrazide structure. Also, the estimated IC50 values can be calculated before the compounds are synthesized using the QSAR equation.